Additive models: extensions and related models - Mammen, Enno; Park, Byeong U.; Schienle, Melanie (SFB 649 discussion paper, 2012)
We give an overview over smooth back tting type estimators in additive models. Moreover we illustrate their wide applicability in models closely related to additive models such as nonparametric regression with dependent error variables where the errors can be transformed to white noise by a linear transformation, nonparametric regression with repeatedly measured data, nonparametric panels with fixed effects, simultaneous nonparametric equation models, and non- and semiparametric autoregression and GARCH-models. We also discuss extensions to varying coeffcient models, additive models with missing observations, and the case of nonstationary covariates. -- smooth backfi tting ; additive models
Keywords: Arbeitspapier; Graue Literatur